Gromov–Witten gauge theory - Frenkel, E; Teleman, C; Tolland, A (Elsevier, 2015)
We introduce a modular completion of the stack of maps from stable marked curves to the quotient stack [pt/C^x], and use this stack to construct some gauge-theoretic analogues of the Gromov-Witten invariants. We also indicate the generalization of these invariants to the quotient stacks [X=C^x], where X is a smooth proper complex algebraic variety.